Modeling Symptoms of Histrionic Personality Disorder Based on Perceived Stress: The Mediating Role of Cognitive Emotion Regulation - Roudi, Gholamali; Adelian, Sahar; Mohseni, Fatemeh; Sagha, Fatemeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: This study aimed to model the symptoms of HPD based on perceived stress with the mediating role of cognitive emotion regulation. Methods and Materials: This study was a descriptive correlational research using structural equation modeling (SEM). The statistical population included undergraduate psychology students from the North Non-Profit University in the 2023-2024 academic year. From this population, 205 students were selected through multistage random sampling as the sample for this study. Data were collected using questionnaires related to HPD symptoms, perceived stress, and cognitive emotion regulation. The data were analyzed using structural equation modeling. Findings: The results indicated that perceived stress is positively associated with HPD symptoms. Additionally, cognitive emotion regulation mediates this relationship. In other words, perceived stress increases HPD symptoms through its effect on cognitive emotion regulation. Conclusion: The findings of this study suggest that cognitive emotion regulation plays a significant role in the relationship between perceived stress and HPD symptoms. Interventions that focus on improving cognitive emotion regulation may be beneficial in treating HPD. Future research should explore the precise mechanisms of the relationship between perceived stress, cognitive emotion regulation, and HPD symptoms. Furthermore, studies should examine whether interventions aimed at improving cognitive emotion regulation can reduce HPD symptoms.